Perspektif Ekonomi Islam Atas Manajemen Operasional Mompreneur (Studi Kasus Di Pawon Eco Lamongan) - Addina Hunafa; Eny Latifah (Trending: Jurnal Manajemen dan Ekonomi, 2023)
The purpose of this study was to find out: (1) operational management of mompreneur at Pawon Eco Lamongan, (2) Islamic economic perspective on operational management of mompreneurs at Pawon Eco Lamongan. This research uses descriptive qualitative method with case study type. To collect data is done by interview, observation, and documentation. To prove the validaty of the data using triangulation. Sources and data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing/verification. The results of the study show that: (1) Operational management of momprenenur at Pawon Eco has 3 main aspects, namely masrketing, production, and finance, in which there are functions including planning starting with the intention, business description, determining the business location, determining the production process, determining the employees, determining the marketing process, and determining the price. Organizing is done by determining employees, determining employee salaries, and determining resellers. Actuating in its implementation considers service quality, material considerations, considers the quality of employees, and the capital used is personal capital. Controlling by means of supervision of product materials, supervision of employees, supervision of market prices, supervision of tools/machines, and supervision of the fulfillment of results for customers. (2) The perspective of Islamic economics on the operational management of mompreneurs at Pawon Eco has generally been carried out in accordance with the principles of Islamic economics, including monotheism, morality, justice, balance, and individual freedom.